Evaluation of corneal biomechanical properties after uneventful standard coaxial phacoemulsification surgery (Annals of Medical Research, 2021)
None
Keywords: Ocular Response Analyzer; Corneal Biomechanical Properties; Coaxial Phacoemulsification Surgery.